Impact of Foreign Trade on Real Gross Domestic Product in Nepal - Thapa , Bhim Kumar (A Bi-annual South Asian Journal of Research & Innovation, 2023)
This research uses yearly time series data from 1975 to 2023 to examine how international trade affects Nepal’s Real Gross Domestic Product (RGDP). The link between import, export and real GDP was investigated in this study using a descriptive and analytical research technique. The Augmented Dickey- Fuller (ADF) stationarity test evaluates data time series features. Descriptive analysis, correlation analysis and regression analysis were used to examine the relationships and measure the impacts. Strong positive relationships between RGDP and import (0.946) and export (0.921) were shown by the correlation study. According to the regression study, import and export both significantly boost RGDP; import has a coefficient of 9.55 while export has a coefficient of 0.50. Approximately 92% of the variance in RGDP can be explained by the regression model, according to the high R-squared value of 0.92. All things considered, the results demonstrate how much international commerce has impacted Nepal’s economic growth.